A study of upwind schemes on the laminar hypersonic heating predictions for the reusable space vehicle. (June 2018) - Qu, Feng; Sun, Di; Zuo, Guang
Abstract: With the rapid development of the Computational Fluid Dynamics (CFD), Accurate computing hypersonic heating is in a high demand for the design of the new generation reusable space vehicle to conduct deep space exploration. In the past years, most researchers try to solve this problem by concentrating on the choice of the upwind schemes or the definition of the cell Reynolds number. However, the cell Reynolds number dependencies and limiter dependencies of the upwind schemes, which are of great importance to their performances in hypersonic heating computations, are concerned by few people. In this paper, we conduct a systematic study on these properties respectively. Results in our test cases show that SLAU (Simple Low-dissipation AUSM-family) is with a much higher level of accuracy and robustness in hypersonic heating predictions. Also, it performs much better in terms of the limiter dependency and the cell Reynolds number dependency. Highlights: Upwind schemes' performances in hypersonic heating predictions are conducted. Upwind schemes' cell Reynolds number dependencies are conducted. Upwind schemes' limiter dependencies are conducted. SLAU is promising to be widely used in the design of the reusable spacecraft.